Increasing Knowledge About Basic Immunization In Village Cihideung Udik Kec. Ciampea Kab. Bogor Jawa Barat - Lela Zakiah; Nurul Azmi Fauziah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
mmunization is an attempt to increase a person's immunity against certain diseases. Community service in the form of counseling on basic immunization in Cihideung Udik Village, Kec. Ciampea, Kab. Bogor, West Java intend to provide information to the public, especially parents who have children aged 0-12 months.